ANALISA KUALITAS LAYANAN THROUGHPUT HANDPHONE DAN MODEM HIGH SPEED DOWNLINK PACKET ACCES (HSDPA) - ., Syamsul Arifin (Jurnal Teknik Elektro Universitas Tanjungpura, 2014)
This study aims to determine the quality of the download throughput using PS R99 ( Mobile ) and HSDPA Modem, with a concomitant growth in the number of users of telecommunications services so that each operator vying to provide the best quality and service, both data and other services. Therefore, the operator themselves must always maintain the quality of data throughput that user remain comfortable with the quality provider. It is necessary for observation of the quality of the throughput on the 3G network uses HSDPA modem of the mobile and the software used is Tems Investigation 8.04 to measure the quality of throughput during the break hour and busy hour. The results of measurements at rest is better than measurement at busy times, measurements using PS R99 (mobile) at recess throughput reached 342.885 Kbps during rush hour reached 313.389 Kbps. While measurement using HSDPA Modem at break hour reached 1459.651 Kbps and at busy hour only reached 866.911 Kbps. And calculation of the break hour throughput reached 1530 Kbps while in busy hour throughput reached 960 Kbps. Keywords-- Throughput PS R99 (Handphone), Modem High Speed Downlink Packet Acces (HSDPA)